2018
DOI: 10.18203/2320-1770.ijrcog20182900
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric hysterectomy: analysis of 50 cases at a tertiary care hospital

Abstract: Background: Despite advances in modern medical sciences, there is a plethora of morbidity which continues to affect women during childbirth, necessitating removal of the uterus in the peripartum or postpartum period. This study analyses 50 cases of obstetric hysterectomy done in a single institute. Methods: After Institutional Ethics Committee approval, a retro prospective analysis of hospital records of 50 cases of obstetric hysterectomy was done over a five year period in the department of obstetrics and gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Incidence in this study is very similar to studies done by Shirodker SD et al and Mayadeo NM et al 7,8 Although the incidence is higher than many other studies done in developed countries and in India because this institution is an important referral centre in this region and most (59.6%; 31/52) of these cases were referred from outside centres in moribund condition after complications have already occurred. [9][10][11] However incidence of EOH was as high as 0.54% and 0.37% in studies done by Singh et al and Sharma et al, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Incidence in this study is very similar to studies done by Shirodker SD et al and Mayadeo NM et al 7,8 Although the incidence is higher than many other studies done in developed countries and in India because this institution is an important referral centre in this region and most (59.6%; 31/52) of these cases were referred from outside centres in moribund condition after complications have already occurred. [9][10][11] However incidence of EOH was as high as 0.54% and 0.37% in studies done by Singh et al and Sharma et al, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Present study is similar to what Mayadeo et al found in India and Abasiattai in Nigeria. 12,14 In this study, uterine atony and uterine rupture are the main causes. Primiparous and pauciparous women who have attempted vaginal delivery outside a health centre are the most affected.…”
Section: Discussionmentioning
confidence: 92%
“…In India this rate varies from 0.12% to 0.57%. [9][10][11][12][13] In Africa, this prevalence varies between 0.2% and 0.62%. [14][15][16] The highest frequency is reported by Nayama et al, in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations